Competition on the Internet - Surblytė, Gintarė (Springer, 2015)
Undeniably widespread and powerful as it is, the Internet is not almighty: it can reach as high as the skies (cloud computing), but it cannot escape competition. Yet, safeguarding competition in “the network of networks” is not without challenges: not only are competitive processes in platform-based industries complex, so is competition law analysis. The latter is often challenged by the difficulties in predicting the outcome of competition, in particular in terms of innovation. Do the specific competition law issues in a digital environment presuppose a reconsideration of competition law concepts and their application? Can current competition law tools be adjusted to the rush pace of dynamic industries? To what extent could competition law be supplemented by regulation – is the latter a foe or rather an ally? This book provides an analysis of recent developments in the most relevant competition law cases in a digital environment on both sides of the Atlantic (the EU and the US) and assesses platform competition issues from a legal as well as an economic point of view.